VISUAL COMMUNICATION DESIGN LEARNING IN EDUCATIONAL INSTITUTION: HAS IT BEEN DISRUPTED? - Nugrahani, Rahina; Triyanto, .; Wibawanto, Wandah (PEOPLE: International Journal of Social Sciences, 2019)
The 4th industrial revolution has brought major changes, not only in technology itself but also in human life, the way humans relate, the way we organize, and including changes in education. Visual communication design learning through educational institution seems to be slow to react the rapid changes and fulfill the demands of society and industry. This paper will discuss how does the 4th Industrial Revolution affects the learning of visual communication design in educational institution. The method used in this study is qualitative approach, which is intended to understand the phenomenon of what is experienced by research subjects. This reseacrh involved a group of students from visual communication design study program. The technique used to obtain data in this research through observation, in-depth interviews and document tracking. This article presented some recommendations for educational institution offering visual arts learning in responding the changes in 4th industrional learning. This article also shows the dynamic of knowledge in the information era has created non-formal learners who are able to develop their own specific materials, methods, and learning strategies